2001
DOI: 10.1007/s101640170013
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behavior of the American oystercatcher Haematopus palliatus pitanay (Murphy 1925) on the intertidal ascidian Pyura praeputialis (Heller 1878) in the Bay of Antofagasta, Chile

Abstract: Oystercatcher foraging behavior has been described for diverse intertidal prey such as limpets, mussels, and oysters. This paper describes foraging behavior of the American oystercatcher, Haematopous palliatus pitanay, on attached and wave-dislodged ascidians, Pyura praeputialis (prey with a restricted geographic range of 70 km) in the Bay of Antofagasta, Chile. Stabbed holes on the top of the ascidian's tunic, probing excursions, handling time, and five prey-handling sequential stages (striking, hammering, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
(4 reference statements)
2
6
0
Order By: Relevance
“…While the propensity of female oystercatchers to eat polychaete worms has been well noted (Baker 1974; Hulscher & Ens 1992; Lauro & Nol 1995), ascidians are much more atypical for the genus. The importance of this item to total diet biomass is similar to results found in Pacheco and Castilla (2001), who studied Haematopus pallitus in Chile and suggested that H. palliatus had learnt to eat local abundances of ascidians (which are not found in most of the species range, Cristian & Castilla 2001); however, sexes were not differentiated. Sex differences in ascidian predation as observed in our study are a reflection of the flexibility of niche divergence in this family, and support the hypothesis that there has been intersexual competitive exclusion in this species whereby the niche divergence has appeared to shift from the mussels and hard‐shelled prey (males)/worms (females) segregation seen in most oystercatcher species to a largely hard‐shelled prey (males)/ascidians (females) divergence in the sooty oystercatcher.…”
Section: Discussionsupporting
confidence: 82%
“…While the propensity of female oystercatchers to eat polychaete worms has been well noted (Baker 1974; Hulscher & Ens 1992; Lauro & Nol 1995), ascidians are much more atypical for the genus. The importance of this item to total diet biomass is similar to results found in Pacheco and Castilla (2001), who studied Haematopus pallitus in Chile and suggested that H. palliatus had learnt to eat local abundances of ascidians (which are not found in most of the species range, Cristian & Castilla 2001); however, sexes were not differentiated. Sex differences in ascidian predation as observed in our study are a reflection of the flexibility of niche divergence in this family, and support the hypothesis that there has been intersexual competitive exclusion in this species whereby the niche divergence has appeared to shift from the mussels and hard‐shelled prey (males)/worms (females) segregation seen in most oystercatcher species to a largely hard‐shelled prey (males)/ascidians (females) divergence in the sooty oystercatcher.…”
Section: Discussionsupporting
confidence: 82%
“…). In addition, beached ascidians seemed to be an important alternative prey for females in Port Elizabeth, Similar feeding behaviour has been described for American pied oystercatchers ( Haematopus palliatus ) in Chile (Pacheco & Castilla ) and female sooty oystercatchers ( H. fuliginosus fuliginosus ) in Australia (Aplin & Cockburn ). In both studies, authors interpreted this uncommon behaviour as a local adaptation to the unusual abundance of Tunicidae and pointed out the niche flexibility of these birds, especially in the case of female sooty oystercatchers.…”
Section: Discussionsupporting
confidence: 63%
“…Some families, for example oystercatchers (Haematopodidae) have a global distribution in species and the different species show similarities in foraging choices and techniques (del Hoyo et al 1996). Oystercatchers feed on a variety of intertidal prey such as oysters Ostea edulis, limpets, Patella vulgata, mussels, Mytilus edulis, periwinkles, Littorina littorea, and polychaetes (Polychaeta) (Hockey 1981, Safriel 1985, Ens et al 1992, Lauro & Nol 1995, Pacheco & Castilla 2001. These different prey types require different feeding techniques and may give a different energetic rewards in relation to their foraging effort (Lauro & Nol 1995, Pacheco & Castilla 2001.…”
mentioning
confidence: 99%
“…Oystercatchers feed on a variety of intertidal prey such as oysters Ostea edulis, limpets, Patella vulgata, mussels, Mytilus edulis, periwinkles, Littorina littorea, and polychaetes (Polychaeta) (Hockey 1981, Safriel 1985, Ens et al 1992, Lauro & Nol 1995, Pacheco & Castilla 2001. These different prey types require different feeding techniques and may give a different energetic rewards in relation to their foraging effort (Lauro & Nol 1995, Pacheco & Castilla 2001. Food availability and territory quality influences not only the survival of the parents but also that of their offspring during the prefledging period (Ens et al 1996, Tjørve et al 2007.…”
mentioning
confidence: 99%